2009
DOI: 10.1108/19355181200900005
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Audit Committee Characteristics, the Contracting Process and Fraudulent Financial Reporting

Abstract: In an effort to restore investor confidence in the wake of recent financial reporting scandals, the Sarbanes‐Oxley Act of 2002 mandates that audit committees be fully independent and have at least one financial expert. The SEC adopted rules implementing these Sarbanes‐Oxley provisions. This paper contributes to the literature on the association between audit committee characteristics recommended by SOX and the likelihood of fraud in two ways. First, we focus on audit committee composition and the extent of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
51
2
12

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(76 citation statements)
references
References 19 publications
7
51
2
12
Order By: Relevance
“…In this study, audit committee independence is found to be insignificant to the reliability of accounting earnings. This observation is consistent with the overall conclusion of Owens-Jackson et al (2009) which state that even a "fully independent audit committee does not totally eliminate fraudulent financial reporting" (p. 62), though the likelihood of fraud is reduced by committee members independence. In addition, the governance structure of a firm may not be effectively reinforced in the presence of high audit committee independence if opportunistic compensation scheme is deployed (as documented in the regression test on ESOS j,t above).…”
Section: Exploratory Statistics Results Interpretation and Discussionsupporting
confidence: 80%
“…In this study, audit committee independence is found to be insignificant to the reliability of accounting earnings. This observation is consistent with the overall conclusion of Owens-Jackson et al (2009) which state that even a "fully independent audit committee does not totally eliminate fraudulent financial reporting" (p. 62), though the likelihood of fraud is reduced by committee members independence. In addition, the governance structure of a firm may not be effectively reinforced in the presence of high audit committee independence if opportunistic compensation scheme is deployed (as documented in the regression test on ESOS j,t above).…”
Section: Exploratory Statistics Results Interpretation and Discussionsupporting
confidence: 80%
“…Bronson et al (2009) find that the advantage of the independent audit committee can only be achieved when the whole audit committee is really independent (100% independent). Jackson et al (2009) also conclude that the probability of fraud is negatively associated with the independent audit committee.…”
Section: Audit Committeementioning
confidence: 97%
“…If audit committee has an effective role, company should present higher quality of financial reports. Bronson et al (2009) and Jackson et al (2009) state that the effectiveness of the audit committee will also affect some characteristics which are proven by previous study: independence, activity, size, and competence of the audit committee. The purpose of audit committee is to monitor management performance, including company's operations and financial reporting.…”
Section: Audit Committee and Probability Of Accounting Fraudmentioning
confidence: 99%
See 1 more Smart Citation
“…These factors stand as non-financial variables that can be used for measuring information asymmetry. The existence and the independence of audit committee are quite important for increasing the quality of information and providing exact information (Jackson, Robinson, & Shelton, 2009). Especially the independence of the board of directors is critical in terms of the quality of financial information (Quan, 2007).…”
Section: The Variables Used For Measuring Information Asymmetrymentioning
confidence: 99%